Determinants of the Implementation of the One House One Jumantik Movement for Dengue Vector Control at Kota Ende Health Center - Pius Kopong Tokan; Krispina Owa; Sulasmi Sulasmi; Hamsir Ahmad; Wahyuni Sahani; Inayah Inayah (Direktorat Politeknik Kesehatan Makassar, 2025)
Background: Dengue fever is a public health issue in Ende Regency at Kota Ende Health Center, an endemic area. Since 2015, the One House One Jumantik movement empowers families, but low awareness and resources hinder implementation. Methods: A qualitative case study with a phenomenological approach from January to June 2025 with six purposively selected informants: technical officers, health center leaders, health office officials, three urban village head. Sample size was determined based on information power and theoretical saturation. Data were collected via observation, open interviews, and document review, then analyzed thematically. Triangulation of sources and techniques ensured validity. Ethical approval was obtained from Poltekkes Kemenkes Kupang (LB.02.03/1/0036/2025). Results: Implementers’ positive understanding supports adoption of the One House One Jumantik program. Nonetheless, budget constraints, limited monitoring structures, weak cross-sector communication, and low community engagement reduce effectiveness. Strengthening coordination, providing training, and applying participatory approaches are key to improving sustainability. Conclusion: The implementation of the One House, One Jumantik movement at Kota Ende Health Center remains limited by resource shortages, organizational structure, and cross-sector coordination. Program effectiveness is affected by organizational capacity, communication, and resource distribution. Addressing these challenges requires concrete actions: conducting cadre training and establishing coordination forums at the Health Center level; providing technical guidance, supervision, and budget support at the District Health Office level; integrating formal policies, planning, and performance monitoring at the Regional Government level; and actively involving the community in inspections and mosquito surveillance